Advancing DNA Steganography with Incorporation of Randomness. (28th May 2020) - Cui, Meiying; Zhang, Yixin
Abstract: DNA has become a promising candidate as a future data storage medium; this makes DNA steganography indispensable in DNA data security. PCR primers are conventional secret keys in DNA steganography. Brute force testing of different primers will be extremely time consuming, and practically unaffordable when high‐throughput sequencing is used. However, the encrypted information can be sequenced and read once the primers are intercepted. A new steganography approach is needed to make the DNA‐encoded information safer, if not unhackable. Mixing information‐carrying DNA with a partially degenerated DNA library containing single or multiple restriction sites, we have built an additional protective layer that can be removed by desired restriction enzymes as secondary secret keys. As PCR is inevitable for reading DNA‐encrypted information, heating will cause reshuffling and generate endonuclease‐resistant mismatched duplexes, especially for DNA with high sequence diversity. Consequently, with the incorporation of randomness, DNA steganography possesses both quantum key distribution (QKD)‐like function for detecting PCR by an interceptor and a self‐destructive property. It is noteworthy that the background noise generated through the protective layer is independent from any sequencing technology including Sanger and high‐throughput sequencing. With a DNA ink incorporating the steganography, we have shown that the authenticity of a piece of writing can be confirmed only by authorized persons with knowledge of all embedded keys. Abstract : Cryptic clues : We show DNA steganography using basic molecular biology techniques with a restriction enzyme as a second secret key: Alice encrypts a message and sends it to Bob. Bob needs a combination of keys 1 and 2 to sequence the DNA and retrieve the information; he can also use qPCR to detect any interception by Eve.